Richesse et diversité floristique de la suberaie de la Mamora (Maroc) - Aafi, Abderrahman; KADMIRI, A A E L (Acta Botanica Malacitana, 2005)
The survey aims to quantify the floristic richeness and diversity of the Mamora’s forest oak-cork ecosystem on the basis of transects and floristic samples distributed according to a stratified and systematic sampling in the different plant formations previously distinguished. The results show that the ecosystem contains 62 families, 261 genders, 408 species, subspecies and varieties : 35 very rare taxa , 29 rare taxa ; 18 endemic taxa, 1 very rare and endemic taxa and 4 rare and endemic taxa. The survey has, otherwise, permitted to reveal the total disappearance of Erica arborea and E. scoparia from this ecosystem and to define the biological spectrum of the studied region, wich is characterized with a clear dominance of therophytes (50.5%).
Keywords: diversity; Mamora; Morocco; Quercus suber; richeness